Pengaruh Emosi dan Lokasi terhadap Kepuasan Pelanggan Indomaret Di Yogyakarta - Thomas Aquinas Radit0; Rizky Teddy Rakhmawan; Meniek Srining Prapti (JEMAP, 2023)
This investigation looked at how location and emotion impacted customer satisfaction at Indomaret in Yogyakarta. 250 respondents made up the sample for this study, and they can be identified by visited Indomaret outlet type, reason for visiting, number of trips to Indomaret in the past month, relationship status, gender, age, employment, and monthly salary. It was used primary survey data, processed and analyzed by multiple regression. The results of the analysis demonstrated that, location and emotions have a significant impact on Indomaret's customer happiness.  The location variable and emotion variable both had positive and significant impact on customer satisfaction.